2016
DOI: 10.1162/jocn_a_00940
|View full text |Cite
|
Sign up to set email alerts
|

Fusiform Gyrus Laterality in Writing Systems with Different Mapping Principles: An Artificial Orthography Training Study

Abstract: Writing systems vary in many ways, making it difficult to account for cross-linguistic neural differences. For example, orthographic processing of Chinese characters activates the midfusiform gyri (mFG) bilaterally, whereas the processing of English words predominantly activates the left mFG. Since Chinese and English vary in visual processing (holistic vs. analytical) and linguistic mapping principle (morphosyllabic vs. alphabetic), either factor could account for mFG laterality differences. We used artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
3
11
0
1
Order By: Relevance
“…One possible factor is the method of instruction experienced as early readers. A set of studies using artificial orthographies (Hirshorn, Wrencher, Durisko, Moore, & Fiez, 2016;Mei et al, 2012;Yoncheva, Blau, Maurer, & McCandliss, 2010;Yoncheva, Wise, & McCandliss, 2015) has demonstrated that visual attention to different grain sizes in print-to-speech mapping, ranging from grapheme-phoneme to whole-word relationships, affects the laterality of neural signatures of visual word processing (i.e., N170 and vOTC activation). When participants were instructed to focus on visual units that mapped onto larger phonological units (e.g., whole word versus phoneme; syllable versus phoneme) they exhibited a relatively more bilateral neural signature.…”
Section: Discussionmentioning
confidence: 99%
“…One possible factor is the method of instruction experienced as early readers. A set of studies using artificial orthographies (Hirshorn, Wrencher, Durisko, Moore, & Fiez, 2016;Mei et al, 2012;Yoncheva, Blau, Maurer, & McCandliss, 2010;Yoncheva, Wise, & McCandliss, 2015) has demonstrated that visual attention to different grain sizes in print-to-speech mapping, ranging from grapheme-phoneme to whole-word relationships, affects the laterality of neural signatures of visual word processing (i.e., N170 and vOTC activation). When participants were instructed to focus on visual units that mapped onto larger phonological units (e.g., whole word versus phoneme; syllable versus phoneme) they exhibited a relatively more bilateral neural signature.…”
Section: Discussionmentioning
confidence: 99%
“…These results support that parietotemporal stimulation affected learning of grapheme-phoneme mappings at the letter level, and did not simply improve route memorization of trained whole word forms. Previous orthographic learning studies have shown that transfer depends on the type of instruction received during training (Bitan et al, 2005 ; Cao et al, 2013 ; Mei et al, 2014 ; Hirshorn et al, 2016 ; Taylor et al, 2017 ), even when training is not on individual letters, but on entire word forms (Yoncheva et al, 2010 , 2015 ). Yoncheva et al ( 2010 ) taught participants to read words using the same orthography, but directed attention to either grapheme-phoneme mappings at the letter level or word level.…”
Section: Discussionmentioning
confidence: 99%
“…HouseFont, FaceFont, and KoreanFont differ visually, but share the same alphabetic mapping principle. To clarify whether the principle of left-lateralization holds true for non-alphabetic orthographies, we turn to Hirshorn et al (2016)’s Faceabary training study in which face images represented English syllables. The study found Faceabary training effects in both the left and right mid-fusiform gyrus, with more bilateral patterns of activation correlated with higher Faceabary reading fluency.…”
Section: Discussionmentioning
confidence: 99%